Evaluating Production Risks, Livelihood Impacts, and Determinants of Agricultural Insurance Demand among Farmers in Ningxia, China - Gao, Zeyuan (JPAIR Multidisciplinary Research, 2025)
This study investigates the production risks, livelihood impacts, and determinants of agricultural insurance demand among farmers in Ningxia, China, a region heavily reliant on agriculture yet vulnerable to various risks. The research highlights the critical role of agricultural insurance as a risk management tool that can stabilize farmer incomes and promote rural economic development. The study employs a quantitative research design, utilizing surveys to gather data from 206 farmers across three rural areas in Ningxia. Key findings reveal that farmers perceive significant risks from natural disasters, price fluctuations, sales issues, and quality risks, which adversely affect their livelihoods. The demand for agricultural insurance is influenced by factors such as insurance policy features, company reputation, individual economic conditions, and the variety of insurance products available. Notably, the study finds no significant differences in evaluations of these factors based on demographic variables such as gender, age, or type of agriculture, indicating that farmers prioritize universal concerns like affordability and reliability over personal characteristics. The results underscore the need for tailored insurance solutions that address the specific challenges faced by farmers in Ningxia, particularly in light of the region’s fragile ecological environment and frequent natural disasters. The study concludes that enhancing the accessibility and effectiveness of agricultural insurance can significantly contribute to the resilience and sustainability of the agricultural sector, ultimately supporting rural livelihoods and economic stability.